Biliary Atresia Relevant Human Induced Pluripotent Stem Cells Recapitulate Key Disease Features in a Dish. Issue 1 (January 2019) - Tian, Lipeng; Ye, Zhaohui; Kafka, Kim; Stewart, Dylan; Anders, Robert; Schwarz, Kathleen B.; Jang, Yoon-Young
Abstract : ABSTRACT: Biliary atresia (BA) is the most common cause of pediatric end-stage liver disease and the etiology is poorly understood. There is no effective therapy for BA partly due to lack of human BA models. Towards developing in vitro human models of BA, disease-specific induced pluripotent stem cells (iPSCs) from 6 BA patients were generated using non-integrating episomal plasmids. In addition, to determine the functional significance of BA-susceptibility genes identified by genome-wide association studies (GWAS) in biliary development, a genome-editing approach was used to create iPSCs with defined mutations in these GWAS BA loci. Using the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 system, isogenic iPSCs deficient in BA-associated genes (GPC1 and ADD3) were created from healthy iPSCs. Both the BA patient-iPSCs and the knock out (KO) iPSCs were studied for their in vitro biliary differentiation potential. These BA-specific iPSCs demonstrated significantly decreased formation of ductal structures, decreased expression of biliary markers including CK7, EpCAM, SOX9, CK19, AE2, and CFTR and increased fibrosis markers such as alpha smooth muscle actin, Loxl2, and Collagen1 compared to controls. Both the patient- and the KO-iPSCs also showed increased yes-associated protein (YAP, a marker of bile duct proliferation/fibrosis). Collagen and YAP were reduced by treatment with the anti-fibrogenic drug pentoxifylline. In summary, these BA-specific human iPSCs showed deficiency in biliary differentiation along with increased fibrosis, the 2 key disease features of BA. These iPSCs can provide new human BA models for understanding the molecular basis of abnormal biliary development and opportunities to identify drugs that have therapeutic effects on BA. Abstract : Supplemental Digital Content is available in the text